IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT AT SD NEGERI 1 CENTRE PATTALLASSANG - Nur Syam; Muhammad Yaumi; Misykat Malik Ibrahim; Muzakkir Muzakkir; Syamsunardi Syamsunardi (Program Studi PGSD Universitas Flores, 2025)
This study aims to examine the impact of the implementation of the Pancasila Student Profile Strengthening Project (P5) on students at SD Negeri 1 Centre Pattallassang, Takalar Regency. Utilizing a descriptive qualitative approach with a phenomenological method, the study involved the principal, teachers from various grade phases, and students as informants. Data collection techniques included participatory observation, in-depth interviews, and documentation. The findings reveal that the implementation of P5 has a broad and profound impact on shaping students’ character, such as honesty, responsibility, independence, cooperation, and awareness of diversity. Moreover, P5 promotes the development of 21st-century skills, including critical thinking, creativity, collaboration, and communication. Project based activities provide students with opportunities to be more active, environmentally conscious, and capable of managing their time and completing tasks independently. The study concludes that the implementation of P5 serves as an effective learning strategy to cultivate students who are intellectually resilient, morally grounded, and socially responsible.